GANT61, a GLI inhibitor, sensitizes glioma cells to the temozolomide treatment. Issue 1 (December 2016) - Li, Jianlong; Cai, Jinquan; Zhao, Shihong; Yao, Kun; Sun, Ying; Li, Yongli; Chen, Lingchao; Li, Ruiyan; Zhai, Xiuwei; Zhang, Junhe; Jiang, Chuanlu
Abstract Background The aim of this study was to investigate the effect of downregulating Hedgehog pathway by GANT61 on human glioma cells, examine the consequent changes of temozolomide (TMZ)-induced effects and explore the molecular mechanisms. Methods The cytotoxicity of a Gli1/2 inhibitor, GANT61 was examined both alone and in combination with TMZ in human glioma cell lines. The mRNA and protein expression alterations were determined by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot, respectively. CCK-8 assay detected the cell proliferative capability. Apoptotic cell number was measured by flow cytometry. The transwell assay was used to test the cell invasive capability. DNA damage effect was identified by COMET assay and γH2AX expression. Results Proliferation of tumor cells treated with GANT61 in combination with TMZ was significantly suppressed compared with those treated with either drug used alone. The combination treatment induced a higher rate of apoptosis, DNA damage and reduced the invasive capability of glioma cells. DNA damage repair enzyme MGMT and the Notch1 pathway increased in the cells treated by TMZ treatment. However, GANT61 could abrogated the protein increasing. Conclusions GANT61 sensitizes glioma cells to TMZ treatment by enhancing DNA damage effect, decreasing MGMT expression and the Notch1 pathway.